Model społecznej gospodarki rynkowej a koncepcja zrównoważonego rozwoju - Nowak, Katarzyna (The Model of Social Market Economy and the Idea of Sustainable Development, 2006)
The article presents some basic issues connected with the role of the government in the development in the light of social market economy and the idea of sustainable development. It is shown that it plays most important part in the field such as environmental policy and in solving social problems (i.e. the exclusion of some market participants or society members). In this context the main question is: How to harmonize the government actions with the postulate of free market? The analysis carried out by the author proves that the model of social market economy (although, from the historical point of view, earlier) could be a form of sustainable development demands realization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 102-115